Correlation of Physical Activity with Behavioral, Emotional, and Psychosocial Disorders: A Cross-Sectional Study of 5 Elementary Schools in Ciherang Village - Agustina Agustina; Fransisca Iriani R Dewi; Lontoh, Susy Olivia; Yohanes Firmansyah; William Gilbert Satyanegara; Valentino Gilbert Lumintang; Kasvana Kasvana; Geoffrey Christian Lo (Community Medicine and Education Journal, 2024)
Physical activity is essential for children, but unfortunately, it has decreased due to the development of technology. Sedentary behavior in children can cause growth disorders, such as obesity, diabetes, heart disease, and high blood pressure. It can also affect child development, including emotional and behavioral disorders, decreased self-confidence, and symptoms of depression. This cross-sectional study was conducted in February-March 2024 in five Ciherang Elementary Schools. The study included 246 children who met the inclusion criteria. Physical activity was assessed using the IPAQ questionnaire, while emotional and behavioral disorders were assessed using the pediatric symptom checklist 17 (PSC-17) questionnaire. Their mean age was 11.83 years. The mean IPAQ score was 62.21 (16.45), and the mean PSC-17 score was 11 (2 – 27). The study found no significant correlation between physical activity and emotional, behavioral, and psychosocial disorders (internalization; p-value = 0.322, attention; p-value=0.515, and externalization; p-value=0.059, and total PSC17 score; p-value=0.944). However, a correlation was found between physical activity and externalizing behavior, with an r-correlation value of 0.121 and an R square of 0.016. Physical activity is associated with externalizing behavior, particularly in children between 10 and 14.